3x = 8y + 11

x + 6y - 8 = 0...which can be written as x = -6y + 8

We now have both equations in the same format. It can be seen that we can make the coefficients of x equal in both equations by multiplying the 2nd equation by 3.

3x = 8y + 11

3x = -18y + 24

If the "lower" equation is then subtracted from the "upper" equation - this eliminates x.

3x - 3x = 8y -(-18y) + 11 - 24

0 = 26y - 13...which can be written as 26y = 13 ; thus y =

3x = (8 x

x + 6y - 8 = 0...which can be written as x = -6y + 8

We now have both equations in the same format. It can be seen that we can make the coefficients of x equal in both equations by multiplying the 2nd equation by 3.

3x = 8y + 11

3x = -18y + 24

If the "lower" equation is then subtracted from the "upper" equation - this eliminates x.

3x - 3x = 8y -(-18y) + 11 - 24

0 = 26y - 13...which can be written as 26y = 13 ; thus y =

^{13}/_{26}=^{1}/_{2}Now substitute for y in either of the original equations to determine x.3x = (8 x

^{1}/_{2}) + 11 : 3x = 4 + 11 = 15 : X =^{15}/_{3}= 5